2015
DOI: 10.1021/acs.jpcb.5b04130
|View full text |Cite
|
Sign up to set email alerts
|

Like-Charge Guanidinium Pairing between Ligand and Receptor: An Unusual Interaction for Drug Discovery and Design?

Abstract: A database survey in this study revealed for the first time that there are 227 counterintuitive like-charge guanidinium pairings (Gdm(+)-Arg pairings) between ligands and receptors in the Protein Data Bank, implying the potential guanidinium-arginine binding between guanidine-containing drugs and their target proteins. Furthermore, there are 145 guanidine-containing molecules in the DrugBank, showing the prevalence of guanidinium groups in drugs. It has also been reported that the introduction of a guanidinium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…confirmed this finding in other systems and defined an electrostatic attraction region in terms of electric field lines. They found that immersion of these complexes in a polarizable medium stabilized them to the point where they became stable relative to the isolated subunits, confirmed by a later analysis of guanidinium pairings . The catalogue of metastable H‐bonded complexes of like charged ions was expanded to dications and dianions.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…confirmed this finding in other systems and defined an electrostatic attraction region in terms of electric field lines. They found that immersion of these complexes in a polarizable medium stabilized them to the point where they became stable relative to the isolated subunits, confirmed by a later analysis of guanidinium pairings . The catalogue of metastable H‐bonded complexes of like charged ions was expanded to dications and dianions.…”
Section: Discussionmentioning
confidence: 87%
“…Examination of ionic liquids provides a number of examples. Cationic guanidinium side chains, for example, can associate with one another in poly‐Arg within aqueous or protein environments . With regard to gas phase systems without recourse to a surrounding polarizable medium to disperse the charges, Weinhold and Klein identified a number of such ion pairs, both cationic and anionic, dubbing them anti‐electrostatic H‐bonds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,[38][39][40] Also, the unusually large number of ligands containing Gdm + groups interacting with Arg amino acids in receptors indicates a potential importance of the like-charge pairing in drug design as well. 41 At the same time, Gdm + ion pairing has also been demonstrated by a combination of capillary electrophoresis and MD simulations. Namely, in electrophoresis experiments it has been observed that addition of GdmCl to the solution of tetraarginine (Arg4) leads to an increased mobility of Arg4, while upon addition of NaCl no mobility enhancement has been observed ( Table 1).…”
Section: Short Arginine-rich Peptides In Watermentioning
confidence: 94%
“…QM/MM methods are especially suitable for studying large biological systems and, to date, have provided molecular‐level insights into many processes, such as the photosensitivity of visual pigments, enzyme catalysis, drug recognition by receptors, and cytotoxic activity mechanisms . It must be stressed that relatively few ONIOM studies have focused on one of the most important groups of biological targets, a family of G protein‐coupled receptors (GPCRs).…”
Section: Introductionmentioning
confidence: 99%